The correlation between cardiac and skeletal muscle pathology in animal models of idiopathic inflammatory myopathies - Prisco, Francesco (Acta Myol, 2020)
Idiopathic inflammatory myopathies (IIMs) represent a heterogeneous group of disorders in which skeletal muscle is inappropriately targeted by the immune system. IIMs are characterized by inflammation of muscle and varying degrees of muscle dysfunction. Extra-muscular manifestations may involve heart, skin, joints, lungs, and gastrointestinal tract. Cardiovascular involvement is a feared event because is one of the leading causes of mortality in IIM patients. As the myocardium shares many features with the skeletal muscle, it is supposed that it can be affected by the same inflammatory processes, which take place during the different forms of IIMs. However, the full extent of this link and the mechanisms behind it are still not fully understood. Animal models have greatly improved our understanding of IIM pathomechanisms and have proven to be a useful tool for discovering therapeutic drug targets. Here we report the evidence of heart muscle involvement in different animal models of spontaneous IIMs, assuming a common autoimmune mechanism and presenting them as study models for human pathology.